Controller Design for Temperature Regulation in a Nonlinear Industrial Heat Exchanger System - Reddy Vakiti Srilatha; Subhadra Harivardhagini; Prananvanand S.; Juliet A. Vimala; Ramesh Gopisetty (E3S Web of Conferences)
A heat exchanger enables heat transfer between two fluids without mixing them. Its performance depends on factors like temperature difference, heat transfer area, and fluid flow rates. Heat exchangers are used in industries such as petroleum refining, food processing, nuclear power, thermal management in spacecraft, and electricity production. This study focuses on designing, modeling, and testing controllers for a nonlinear heat exchanger system. Initially, the baseline performance is evaluated, followed by an analysis of system behavior under various conditions. The transient response and error criteria of control strategies are assessed through setpoint tracking. MATLAB is used to implement the control algorithm, allowing real-time monitoring of the system’s input and output for different setpoints. The controller adjusts to ensure optimal heat transfer and performance.